Judicial Control of Discretionary Power Used in Administrative Rule-making - Kilasonia, Nino (Journal of Law, 2018)
This article analyzes standards of judicial scrutiny used by the Georgian and the US Supreme Courts to ensure effective control of discretionary power utilized in administrative rulemaking. The first chapter discusses the US Supreme Court’s interpretation of the Administrative Procedure Act’s (further APA) “arbitrary and capricious” standard of review. Then it explores importance of hard look and deference doctrines. The second chapter studies the Georgian Supreme Court’s approach toward judicial control of discretionary power used in administrative rulemaking. The conclusion summarizes findings of the research.